2019
DOI: 10.1088/1757-899x/584/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on torsional behavior of fiberious reifoced concrete beams with different concrete strength

Abstract: This study is intended to deal with twelve reinforced concrete beams cast into three categories of Concrete type with Normal, Self Compacted and High Strength Concrete. Two beams of each category have steel fibers and the other used as reference one. Test results are presented in graphs also listed in Tables. Test results indicated that, category of High Strength Concrete beams is the strongest category depending onto the ultimate load capacity and the highest stiffness, followed by the Self Compacted Concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous studies have found that increased compressive strength of concrete leads to an increase in total torque capacity [12]. Increased steel fiber content in the cross-section reduces the angle of twisting of the reinforced concrete beam and increases the stiffness of the beam [13,14].…”
Section: Compacting Concrete Hollow -Behavior Of Steel Fiber Self Dee...mentioning
confidence: 99%
“…Previous studies have found that increased compressive strength of concrete leads to an increase in total torque capacity [12]. Increased steel fiber content in the cross-section reduces the angle of twisting of the reinforced concrete beam and increases the stiffness of the beam [13,14].…”
Section: Compacting Concrete Hollow -Behavior Of Steel Fiber Self Dee...mentioning
confidence: 99%